Penerapan Analisis Standar Belanja Bagi Pengawas Internal Pemerintah Daerah - Maylen P. Kambuaya; Hastutie Noor Andriati (The Community Engagement Journal, 2020)
Training "Preparation Of Spending Standard Analysis Model (Asb) In Waropen District", which aims to know the fairness of financial budget and determine the model of analysis of spending standards that meet the fairness of education and training activities in the Waropen District Device Organization. The method used in this study is by approaching the cost performance of activities (ABC) and simple regression approach. While the data used is secondary data, in the form of existing activities of local government in the current year (in the form of Draft Budget Work or Budget Implementation Document - Regional Work Equipment Unit) and also secondary data in the form of unit price standards. Proposed budgets that do not comply with the ASB will be analyzed or revised according to the established standards. The draft APBD is prepared based on the results of an assessment of the proposed budget of SKPD which is prepared based on ASB. For local governments, the Analysis of Spending Standards is expected to hold effective and efficient budget management and accountability of local governments that will later materialize good governance. Based on the explanation above, it appears that the existence of a standard analysis of shopping is a must. Without the analysis of spending standards, the APBD proposed by each SKPD will tend not to comply with the budget standards. As a result, the preparation of performance-based budgets that are expected to be able to improve the performance, efficiency, effectiveness, and accountability of local governments.